Digital Tool Supporting the Documentation and Analysis of Cultural Heritage: The Case of the Analytical 3D Model of the Zamość Fortress - WAC, Michał; SZOSTAK, Bartosz (Computer Assisted Methods in Engineering and Science, 2026)
This paper presents a city-scale digital documentation and analysis workflow for cultural heritage assets, demonstrated on the example of the UNESCO-listed historic centre and fortress area of Zamość (Poland). The study integrates terrestrial laser scanning (TLS) with unmanned aerial vehicle (UAV) and terrestrial photogrammetry to produce a geometrically consistent 3D dataset covering over 100 buildings and key public-space elements. The processing pipeline includes scan registration, image-based reconstruction, and cross-sensor alignment, followed by the creation of an analytical 3D model segmented by address and parcel identifiers to enable linkage with municipal datasets. A semantic layer is implemented by assigning a structured set of building- and neighbourhood-level parameters and mapping them into building information modelling (BIM)/openBIM structures (Revit shared parameters and industry foundation classes (IFC) Property Sets), targeting a level of information adequate for conservation-oriented diagnostics and urban-scale assessments rather than detailed component-level historic building information modelling (HBIM). Geometric quality is verified using independent checkpoints and registration statistics (e.g., root mean square error (RMSE) where applicable), yielding a typical spatial agreement on the order of 4 cm to 5 cm for the integrated model in representative test areas. The resulting environment supports multi-criteria querying and visualisation, including functional categorisation, technical condition screening (e.g., moisture-related indicators), and energy-related attributes for prioritisation at the district scale. The main contribution is a reproducible integration of multi-source survey data with an explicit semantic/BIM mapping and verifiable accuracy reporting for a heritage city context, clarifying which outputs stem from the proposed method (data integration, segmentation, semantic schema, and validation) versus the standard capabilities of the employed software.